2018
DOI: 10.1002/zaac.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Molecular and Electronic Structures of μ‐Oxo Diferric Complexes with the Bridging Motive

Abstract: The complexes [(susan){FeIII(OAc)(μ‐O)FeIII(OAc)}](ClO4)2, [(susan){FeIII(μ‐O)(μ‐OAc)FeIII}](ClO4)3, and [(susan){FeIII(μ‐O)(μ‐CO3)FeIII}](ClO4)2 (susan = 4,7‐dimethyl‐1,1,10,10‐tetra(2‐pyridylmethyl)‐1,4,7,10‐tetraazadecane) were synthesized and characterized. Prominent IR vibrations do not shift from the solid state to CH3CN solutions demonstrating dissolution without structural rearrangements or substitutions. The acetates in [(susan){FeIII(OAc)(μ‐O)FeIII(OAc)}]2+ are in a trans conformation resulting in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 27 publications
0
27
1
Order By: Relevance
“…In accordance to the assignment of Solomon and coworkers, the transition at 17250 cm ‐1 should correspond to the 6 A 1 → 4 T 2 transition. However, in a recent study on doubly‐bridged diferric complexes of susan, we already found inconsistencies in the series for this assignment . Thus, it seems likely that the transitions between 17000 – 18000 cm ‐1 contain also some µ‐O→Fe III LMCT character.…”
Section: Results and Analysismentioning
confidence: 83%
“…In accordance to the assignment of Solomon and coworkers, the transition at 17250 cm ‐1 should correspond to the 6 A 1 → 4 T 2 transition. However, in a recent study on doubly‐bridged diferric complexes of susan, we already found inconsistencies in the series for this assignment . Thus, it seems likely that the transitions between 17000 – 18000 cm ‐1 contain also some µ‐O→Fe III LMCT character.…”
Section: Results and Analysismentioning
confidence: 83%
“…We studied the μ-oxo-bridged diiron complexes intensively by magnetic, electrochemical, and spectroscopic means. [45,66,[69][70][71] It turned out, that the UV-Vis-NIR spectroscopic and magnetic properties are only slightly depending on the nature of the anionic ligand X À in the mono-μ-oxo-bridged complexes [(susan){Fe III X(μ-O)Fe III X}] 2 + . [66] However, the variation of the bridging mode from mono-bridged μ-oxo to doublybridged μ-oxo,μ-carboxylato results in strong differences in the UV-Vis-NIR spectra, which is known from tpa-based complexes.…”
Section: A Ph-driven Reversible Carboxylate-shift Observed In Solutiomentioning
confidence: 99%
“…[45,46] The electrochemical characterization of the μ-oxo-bridged diferric complexes of the ligand susan [(susan){Fe III X(μ-O)Fe III X}] 2 + reveal irreversible oxidation processes. [45,70,71] The peak potential in V vs Fc + /Fc of these oxidations span a large range depending on the exogenous ligand X: Cl À 1.48, OAc À 1.45, F À 1.40, OMe À 1.14, and OH À 0.79. It is interesting that in such an isostructural series the variation of only one ligand can influence this redox potential so strongly.…”
Section: Influence Of the Terminal And Exogenous Donors On Redox Potementioning
confidence: 99%
See 2 more Smart Citations